Sea Ice Modulates Air–Sea Methane Flux in the Southern Ocean - Gong Zhang; Qinghua Yang; Bo Han; John Prytherch; Brett F. Thornton; Dake Chen (Geophysical Research Letters)
Abstract The Southern Ocean (SO) is predicted to be a weak sink for atmospheric CH4, although the magnitude is uncertain due to a lack of observations of the marginal ice zone (MIZ). Using both eddy covariance and bulk formula flux measurements from the icebreaker R/V Xuelong2, we found that the eastern SO during an austral summer was a sink for CH4. The strongest downward CH4 fluxes occurred in areas of low sea ice concentration (10%–40%), where sea‐ice melting resulted in low temperature and salinity, increasing CH4 solubility. The CH4 fluxes are weak in regions of high sea ice concentration (>50%) due to the blocking effect of sea ice. We estimate that the uptake of CH4 during one summer month in the study region offsets 1.2%–2.6% of annual global oceanic CH4 emissions. Suggesting that the Antarctic MIZ is more important in the global CH4 budget than previously thought.